Development of an AR based method for augmentation of 3D CAD data onto a real ship block image. (May 2018) - Kim, Daewoon; Park, Jungseo; Ko, Kwang Hee
Abstract: This paper proposes a method for augmenting a 3D CAD model of a ship block onto an image using an augmented reality technique. A two-dimensional image that captures a ship block is obtained using a digital camera. The image is processed to extract a feature of the block for establishing the correspondence between the block in the image and the 3D CAD model. In this work, a rectangular planar region is used as the feature in the image, which is then compared with face components in the CAD model. Once the correspondence is found, the initial pose of the block is computed using the correspondence information, and the CAD model is then augmented onto the image using the initial pose. Next, a registration process is employed to reduce the registration error further using a Lie Algebra-based method, which iteratively approximates the correct pose while reducing the error. As an option, a manual procedure is provided to allow a user to select the corresponding face for initial pose estimation. Real examples are used for testing the proposed method.